2020
DOI: 10.3390/d12010024
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Field-Realistic Exposure of Honeybee Colonies to Neonicotinoids by An Integrative Approach: A Case Study in Romania

Abstract: Honeybees (Apis mellifera L.) are excellent biosensors that can be managed to collect valuable information about environmental contamination. The main objective of the present study was to design and apply an integrative protocol to monitor honeybee colony activity and sample collection by using electronic technologies combined with classical methods in order to evaluate the exposure of honeybees to the neonicotinoids that are used in melliferous intensive crops. The monitored honeybee colonies were especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…As a response to colony collapse disorder (CCD), where major decrease in honeybee colonies is reported all over the word [6][7][8], advancement in technology is playing a major role in preserving honeybee's species, pollination, and biodiversity sustainability [9,10]. In that context, Industry 4.0 and IoT technologies are playing a major role [11], where the use of sensors, networking, and artificial intelligence (AI) in addition to models, simulations, and process discovery are transforming current industrial processes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As a response to colony collapse disorder (CCD), where major decrease in honeybee colonies is reported all over the word [6][7][8], advancement in technology is playing a major role in preserving honeybee's species, pollination, and biodiversity sustainability [9,10]. In that context, Industry 4.0 and IoT technologies are playing a major role [11], where the use of sensors, networking, and artificial intelligence (AI) in addition to models, simulations, and process discovery are transforming current industrial processes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Later, an integrative protocol was developed for monitoring the effects of field-realistic exposure of honey bees to neonicotinoids by monitoring honeybee colony activity along with electronic measurements of internal and external hive temperture and humidity as well as colony weight. It was found that quality samples preparation and follow up of honeybee colonies and honey/pollen flows can be successfully performed by using classic methods to monitor weather conditions; activities and population of colonies; weight gain; or contemporary technologies, including electronic sensors combined with the Internet of Things and big data storage [20].…”
mentioning
confidence: 99%